ANALISIS ANGKA KEBUTUHAN NYATA OPERASI DAN PEMELIHARAAN (AKNOP) JARINGAN IRIGASI DAERAH IRIGASI MANGANTI - Suswanti, Desi; maskur, atep; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2025)
Strategies for increasing food production, especially in terms of agriculture, are very necessary to meet increasing food needs. One strategy is to improve the irrigation system through periodic and routine evaluation and assessment. From the results of surveys and research carried out in the Manganti Irrigation Area (DI) it was found that several points of damage were related to channels or canals that were covered with rubbish or sediment. The Manganti Irrigation Area (DI) received a performance index assessment of 78.12% with a physical infrastructure aspect value of 33.29%, plant productivity of 12.75%, supporting facilities for Operation and Maintenance (O&M) of 6.40%, personnel organization of 14.43%, documentation 4.02%, water user farmer associations (P3A) 7.23%. Furthermore, the results of the calculation of the Operation and Maintenance Real Adequacy Figure (AKNOP) in the Manganti Irrigation Area (DI) showed that the Operation and Maintenance Real Adequacy Figure was IDR. 289,237,711.00